A novel convolutional transfer feature discrimination network for unbalanced fault diagnosis under variable rotational speeds. (19th August 2019) - Xu, Kun; Li, Shunming; Wang, Jinrui; An, Zenghui; Qian, Weiwei; Ma, Huijie
Abstract: Deep learning has been widely used in the field of fault diagnosis due to its excellent performance in feature extraction and has been gradually applied to solve various problems in fault diagnosis. Convolutional neural networks and transfer learning networks have been gradually employed to solve the problems of sample imbalance and domain adaptation under variable rotational speeds in fault diagnosis. However, there are still some weaknesses in current research. Firstly, sample imbalance in fault diagnosis is accompanied by the domain-adaptive problem in practice. Secondly, transfer learning cannot extract domain-invariant features that do not change with the rotational speed, which leads to poor diagnosis results when it is applied to other working conditions without transferring the rotating speed. To solve the above problems, an architecture named a convolutional transfer feature discrimination network (CTFDN) is proposed in this paper. It uses the scaled exponential linear unit activation function, and the main body adopts a two-branch network architecture of weight sharing, which mainly includes a deep feature extraction network for fusion feature extraction, a transfer learning network for domain-adaptive problems, and an unbalanced-sample feature discrimination network for feature similarity determination. Finally, two fault datasets are used to test the validity of the proposed model. The results show that the CTFDN model can extract domain-invariant features well in unbalanced fault sample information, and still has good diagnostic accuracy under variable rotational speeds.